Derailed: A Detective Ravn Thriller - Krefeld, Michael Katz (Saga Egmont, 2023)
New propulsive thriller from Denmark's King of Crime.Criminal investigator Thomas Ravnsholdt—better known as Ravn—is on leave from Copenhagen's special crime unit following the brutal murder of his wife.Racked with guilt over her death, Ravn must navigate the seedy underbelly of Stockholm he'd hoped to leave behind when he is informed of a young woman's strange disappearance. As he races to determine if the woman is still alive, Ravn's investigation takes a dangerous turn when he is drawn into the web of a sadistic murderer... Can he find the missing woman before it's too late?Fast-paced, moody, and atmospheric, "Derailed" is the first book in another exciting, international-bestselling series from Michael Katz Krefeld, award-winning author of the Inspector Cecilie Mars Thrillers.-